Information and Insurer Financial Strength Ratings: Do Short Sellers Anticipate Ratings Changes?. Issue 2 (24th February 2015) - Wade, Chip; Liebenberg, Andre; Blau, Benjamin M.
Abstract: Ratings of financial institutions have been shown to provide informational value as stock prices generally decrease in response to ratings downgrades. Moreover, insurer's stock prices have been observed to decrease 2 days prior to downgrades, suggesting that informed trading occurs during the predowngrade period. This study examines the trading activity of short sellers surrounding insurer financial strength ratings. We show that short selling is abnormally high during the predowngrade period—indicating that short sellers can predict rating downgrades. Interestingly, we find that predowngrade short selling is driven by stocks of insurers with the most transparent balance sheets. This result suggests that while short sellers can predict rating downgrades generally, the opaqueness of an insurer's assets and liabilities can inhibit informed trading during the predowngrade period.